PD-1-siRNA Delivered by Attenuated Salmonella Enhances the Antitumor Effect of Chloroquine in Colon Cancer - Lu, Shuya; Gao, Jianhui; Jia, Huijie; Li, Yang; Duan, Yongbin; Song, Fuyang; Liu, Zhiang; Ma, Shuai; Wang, Mingyong; Zhao, Tiesuo; Zhong, Jiateng (Frontiers in Immunology, 2021)
The widespread appearance of drug tolerance and the low efficiency of single treatment have severely affected the survival time of the patients with colorectal cancer. Exploring new treatment options and combined treatment strategies have become the key to improving the prognosis. The combination of immunotherapy and chemotherapy have shown good clinical expectations. Here, we studied the cooperative effects of chloroquine, an anti-malarial drug that is now widely used in anti-tumor research, and RNA interference (RNAi) targeting the immune checkpoint molecule Programmed Death-1 (PD-1) delivered with attenuated Salmonella. Our results show that chloroquine can not only significantly inhibit the survival of colon cancer cells and induce apoptosis, but also effectively inhibit cell invasion and migration. The results of in vivo experiments show that chloroquine can increase the expression of PD-1 in tumor tissues. Combining chloroquine and PD-1 siRNA can further inhibit the growth and metastases of colon cancer and induce apoptosis. The mechanism underlying this phenomenon is the occurrence of chloroquine-induced apoptosis and the effective immune response caused by the attenuated Salmonella carrying PD-1 siRNA. This study suggests that the combined application of PD-1-based immunotherapy and anti-cancer drugs has become a new expectation for clinical treatment of colorectal cancer.